High‐Temperature Structural Transformations of 1, 1‐Diamino‐2, 2‐dinitroethene (FOX‐7). Issue 6 (24th August 2016) - Zakharov, Viktor V.; Chukanov, Nikita V.; Dremova, Nadezdha N.; Chervonnyi, Alexandr D.; Shilov, Gennadiy V.; Korsounskii, Boris L.; Kazakov, Anatoliy I.; Volkova, Nina N.
Abstract: Stuctural transformations of 1, 1‐diamino‐2, 2‐dinitroethene (FOX‐7) were investigated in the temperature range 298–513 K by means of DSC, TG, isothermal calorimetry, PXRD, IR spectroscopy, and electron microscopy. The data obtained confirm the existence of the high‐temperature δ‐FOX‐7 polymorph stable above 480 K. The heat effect of the γ→δ transformation is − 4.6 J g −1 (−680 J mol −1 ). Metastable γ‐phase formed in the reverse process δ→γ has a perfect crystal structure and is stable towards thermal decomposition. Possible mechanisms of sharp deceleration of thermal decomposition of FOX‐7 at the 40 % conversion are discussed. Abstract :